What Can Economists Learn from Happiness Research? - Frey, Bruno S; Stutzer, Alois (Journal of Economic Literature, 2002)
Happiness is generally considered to be an ultimate goal in life; virtually everybody wants to be happy. The United States Declaration of Independence of 1776 takes it as a self-evident truth that the “pursuit of happiness” is an “unalienable right”, comparable to life and liberty. It follows that economics is – or should be – about individual happiness. In particular, the question is how do economic growth, unemployment and inflation, as well as institutional factors such as good governance, affect individual well-being? In addition to this intrinsic interest, there are three major reasons for economists to consider happiness. The first is economic policy. At the micro-level, it is often impossible to make a Pareto-optimal proposal, because a social action entails costs for some individuals. Hence an evaluation of the net effects, in terms of individual utilities, is needed. On an aggregate level, economic policy must deal with trade-offs, especially those between unemployment and inflation. Using happiness data for twelve European countries and the period 1975 to 1991, it has (cautiously) been calculated that a one percentage point increase in the unemployment rate is marginally compensated for by a 1.7 percentage point decrease in inflation (Rafael Di Tella, Robert MacCulloch, and Andrew Oswald 2001). This result significantly deviates from the “misery index ” which, for lack of information, has simply been defined as the sum of the percent unemployment rate and the percent annual inflation rate. Another trade-off that can be